The Association between Religious Activities Participation and Physical Function in Indonesian Elderly - Ekadinata, Nopryan; Imamah, Nur Fithriyanti; Nurhidayati, Evi (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2024)
Physical function difficulty is a big concern in the elderly globally. Previous studies highlighted the inconclusive findings regarding the elderly's religious involvement and physical function disability. Furthermore, spiritual study is still scarce in Asian settings. The study examined the association between religious involvement (majelis taklim) and physical disability. This cross-sectional observational study harnessed the fifth wave of the Indonesian Family Life Survey (IFLS). Katz Index was used to measure the occurrence of physical disability. Participants aged ≥ 60 years were involved (n = 1799), and 18% reported having a physical function disability. Binomial logistic regression showed that in the unadjusted model, participation in majelis taklim (OR = 0.86, p 0.01) and involvement in the religious program (OR = 0.72, p0.05) were significantly associated with having no physical disability. Meanwhile, the lower frequency of participation in majelis taklim was significant with physical disability in the adjusted model (OR = 0.89; 95%, p0.05).  Participation in religious activities was associated with a lower probability of having a physical function disability in the elderly. The result of the study can be a potential consideration for caregivers, health workers, and policymakers to maximize the religiosity involvement program for reducing the risk of physical disability among the elderly.